Emotional numbing and lessons learned after a violent conflict - Experimental evidence from Ambon, Indonesia - Katharina Werner; Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2016)
Violent conflict is sometimes believed to provoke discrimination, but sometimes also seen to reduce pro-sociality in general. While discrimination may reinforce conflict, a lack of pro-sociality hinders peace reconciliation, social capital formation and development. We test which of these viewpoints finds support and how activation of memories of the conflict affects people's pro-social behavior. Lab-in-the-field experiments were run among Muslim and Christian students in post-conflict Ambon, Indonesia, and combined with data from a post-experimental questionnaire. With the help of dictator, ultimatum and trust games, we investigate the impact of activation of memories of the conflict on different types of pro-sociality. We do not find evidence for discrimination against out-group members. Instead, pro-sociality is significantly reduced if subjects are reminded of the conflict. This effect is particularly strong if subjects had been highly exposed to violence and thus particularly dismal memories were activated. Our findings run counter to the viewpoint that conflict, group identities and discrimination reinforce each other and lead to a downward spiral. They are supportive of emotional numbing. Subjects behave pro-socially, potentially due to the lessons learned from the conflict, unless memories of the conflict are activated. For peace reconciliation, it is thus important to avoid activation of such memories.
Keywords: C93; Z12; Z13; 330; Conflict resolution; Religion; Ethnicity; Discrimination; Experiment; Conflict exposure